KELEBIHAN BEBAN KERJA DAN STRES DAPAT MENYEBABKAN POLISI MEMBUNUH DAN BUNUH DIRI - Tugimin Supriyadi; Nadiya Alfira; Octo Iskandar (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The National Police of the Republic of Indonesia is a service organization that has the responsibility to maintain order and peace in the country by enforcing the law and reducing criminal activities. Working as a police officer is closely related to discipline. As state servants, police officers are required to have discipline in carrying out their duties. The police have quite heavy duties and responsibilities, and there are stress triggers due to having to deal with traumatic events that have a physical and mental impact, such as violence, murder, suicide, situations of abuse, and seeing corpses. Police killings and suicides are certainly a serious concern for the police and society. Stress is the body's reaction to changes that require physical, psychological and emotional response, regulation and/or adaptation. Stress can originate from situations, conditions, thoughts, and/or cause frustration, anger, nervousness, and anxiety. Pressure that comes from ourselves and the external environment that is beyond our control or exceeds the limits of our internal ability to handle. Stress usually shows feelings when someone is stuck with a problem that they cannot overcome. Work stress is a person's condition when faced with opportunities/opportunities, obstacles or demands which become a dynamic condition for a person. The trigger factors are work stress, including environmental, organizational and workload. This is inseparable from the fact that police have high work demands, so it is not uncommon for them to desert or take extreme measures, such as committing suicide